The Role Of Student Community Engagement Participants As Teaching Personnel In Educational Assistance Efforts Through The Smart Village Program In Jejel Village - Buyun Khulel; Khoirul Huda; Sinta Zakiyah Maghfiroh; Nur Ziana; Nanda Fitrotun Mukaromah (Shof Journal of Social Impact, 2024)
The form of community service carried out by students is a real work lecture (KKN). To educate the nation's life, one of the activities that needs to be carried out by KKN students is activities in the field of education. In the implementation of education, of course, it requires teaching staff whose job is to teach, whether teaching in formal or non-formal education. We carried out the Real Work Lecture (KKN) in Jejel Village, Ngimbang District, Lamongan Regency. Our goal of doing KKN in the village is to do community service and help increase interest in learning in the village children. Thus, this article has the title The Role of KKN Students as Teachers in Education Assistance Efforts Through the Smart Village Program in Jejel Village. This Smart Village Program can be carried out well and produces several formal and non-formal education activities, namely being a teacher at PAUD, TK, SD, and TPQ, teaching free tutoring, and providing computer tutoring.